Sejarah Perkembangan Linguistik Arab Klasik - Nurul Islamia, Fadlia; Sugito, Sugito; Tatang, Tatang; Khoirunisa, Siti; Susiawati, Iis (Ta'limi | Journal of Arabic Education and Arabic Studies, 2026)
Arabic holds a special position in the history of Islamic civilization because it functions not only as a means of communication, but also as a medium for conveying the Divine revelation through the Qur’an and the Hadith of Prophet Muhammad ﷺ. As Islam expanded into non-Arab regions, there emerged a need to preserve the purity and clarity of the Arabic language through the establishment of systematic linguistic rules. This study employs a historical-comparative method to trace the development of classical Arabic linguistics and to analyze the contributions of key figures such as Khalīl ibn Aḥmad al-Farahīdī and Sibawaih in the standardization of Arabic grammar. Based on a review of relevant literature, it was found that the development of classical Arabic took place through four major periods: the Jahiliyyah period, the early Islamic period, the Umayyad period, and the Abbasid period. Each period demonstrates significant changes in social, political, and intellectual aspects that influenced the structure and function of the Arabic language. During the Abbasid era, Arabic linguistics reached its peak through monumental works such as Kitāb al-‘Ayn and Al-Kitāb, which established the systematic foundations of Arabic phonology and grammar. Therefore, it can be concluded that the development of classical Arabic linguistics is the result of a long and dynamic intellectual process influenced by the interaction between religion, culture, and the scholarly thought of language experts.